Development of “Berbudi” (Learning Indonesian Culture) Interactive Learning Media Using Articulate Storyline in the IPAS Subject for Fourth-Grade Students at SD Negeri 2 Puru, Trenggalek Regency - Anis Ekowati; Ria Fajrin Rizqy Ana; Imam Sukwatus Suja'i (SOSIOEDUKASI, 2026)
The rapid development of digital technology in the globalization era demands innovation in learning resources that can present material concretely; however, in reality, IPAS learning on cultural diversity in schools is still dominated by lecture methods that tend to be abstract and less engaging for students. This study aims to: (1) describe the development process of "Berbudi" interactive learning media using the ADDIE model; (2) test the validity of the media based on expert judgment; (3) analyze the practicality of the media; and (4) measure the effectiveness of the media in improving learning outcomes for IPAS subjects, specifically on cultural diversity material for fourth-grade students at SD Negeri 2 Puru, Trenggalek. This is a Research and Development (R&D) study employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fourth-grade students of SD Negeri 2 Puru. Data collection instruments included expert validation sheets, teacher and student response questionnaires, and learning outcome tests (pre-test and post-test). The results showed that: (1) Berbudi media was declared highly valid with an average score from material, media, and language experts of 92.68%; (2) the media was declared highly practical based on teacher responses (95.83%) and student responses (91.67%); (3) the media was declared highly effective with a significant increase in learning outcomes, as indicated by an average N-Gain score of 0.72 (high category). The conclusion of this study is that the Articulate Storyline-based Berbudi interactive learning media is feasible and effective for use as an independent learning resource to enhance students' understanding of Indonesian cultural diversity within the Merdeka Curriculum